2022
DOI: 10.1038/s41598-022-06115-9
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin is negatively associated with disease activity and Sharp score in treatment-naïve Han Chinese rheumatoid arthritis patients

Abstract: The association and potential role of the protein hormone adiponectin in autoimmune diseases causing musculoskeletal disorders, including rheumatoid arthritis (RA), are controversial. Conflicting results may arise from the influences of confounding factors linked to genetic backgrounds, disease stage, disease-modifying anti-rheumatic drugs and patients’ metabolic characteristics. Here, we examined serum level of adiponectin and its relationship with disease activity score 28 with erythrocytes sedimentation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Studies have indicated that adiponectin exhibits antidiabetic and vasculo-protective effects [ 37 ]. Inverse or favorable and direct or paradoxically unfavorable associations of adiponectin concentrations were observed in many studies attributing to the metabolic risk factors in RA [ 38 - 40 ]. In our study adiponectin was found to be decreased in RA patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that adiponectin exhibits antidiabetic and vasculo-protective effects [ 37 ]. Inverse or favorable and direct or paradoxically unfavorable associations of adiponectin concentrations were observed in many studies attributing to the metabolic risk factors in RA [ 38 - 40 ]. In our study adiponectin was found to be decreased in RA patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies suggest that in newly-diagnosed RA, adiponectin exerts mainly anti-inflammatory effects, but pro-inflammatory effects of adiponectin are observed in patients with advanced disease. Chen et al have shown a negative correlation between plasma adiponectin levels and disease activity parameters in newly diagnosed RA patients [ 43 ], while in studies including patients with advanced disease, a positive correlation of adiponectin with disease process activity parameters was observed [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations [200,[260][261][262]265,272,275,277,278] have found a positive correlation between adiponectin serum levels and disease activity or radiographic progression. Nevertheless, this association is not universally acknowledged, as other studies have produced contradictory findings [202,219,223,258,268,279]. Baker et al [276] recently found that adiponectin levels were strongly associated with radiographic damage, seropositivity, longer disease duration, prednisone use, and circulating inflammatory cytokines in people with rheumatoid arthritis.…”
Section: Adiponectinmentioning
confidence: 99%